C-Reactive Protein to Albumin Ratio Predicts 30-Day and 1-Year Mortality in Postoperative Patients after Admission to the Intensive Care Unit - Oh, Tak Kyu (J Clin Med, 2018)
C-reactive protein and albumin are associated with poor outcomes in critically ill patients. This study aimed to investigate the significance of the C-reactive protein/albumin (CRP/ALB) ratio as a novel prognostic factor for 30-day or 1-year mortality after admission to the postoperative intensive care unit (ICU). This retrospective study was conducted by examining the medical records of postoperative patients aged 19 years or older admitted to the ICU at a tertiary care hospital from January 2007 to July 2016. This study included data on 11,832 postoperative patients in the analysis. The cut-off value of the CRP/ALB ratio was set at 1.75 and 1.58 for 30-day and 1-year mortality after ICU admission, respectively. In postoperative patients with a high CRP/ALB ratio (>1.75 or >1.58), the probability of death within 30 days or 1 year after ICU admission were 30% or 43% higher than that in the group with the least CRP/ALB ratio, respectively (≤1.75 or ≤1.58)(p < 0.05). This study found the CRP/ALB ratio measured immediately after ICU admission to be an independent risk factor for 30-day and 1-year mortality in postoperative patients admitted to the ICU.